Analisis Kebijakan Program Rumah Gratis Siap Huni pada Koperasi Syariah Benteng Mikro Indonesia dalam Perspektif Ekonomi Islam - Aenul Fadillah; Kisanda Midisen; MH Ainulyaqin; Sarwo edy (Economic Reviews Journal, 2024)
This study aims to determine the policy of the free housing program ready for habitation and to determine the free housing program ready for habitation from an Islamic point of view and to determine the relationship between the free housing program ready for habitation in the Benteng Micro Indonesia Sharia cooperative and Islamic economics. The type of research used is qualitative research with a phenomenological approach that is by using primary data in the form of interviews and observations, as well as documentation then secondary data in the form of collection in the form of journals, scientific papers, dictionaries, relevant reading literature. The results of the study show that the ready-to-live-in housing program run by the Benteng Micro Indonesia sharia cooperative is really provided free of charge to its members and the general public without incurring any costs for development from the beneficiaries. In order to get a free, ready-to-live house run by the Benteng Micro Indonesia Sharia cooperative, prospective beneficiaries must follow a policy by fulfilling specific criteria and conditions that have been determined by the director of the Benteng Micro Indonesia Sharia cooperative. Then Islamic economic experts argued that the free housing program is permissible in Islam, because the free housing program is a commendable social activity to help the poor in meeting their basic needs, one of which is housing. As well as the free housing program, which is ready for habitation, is very closely related to the Islamic economy because every economic development, especially for the benefit of Muslims, will relate to and also affect the Islamic economy